p53 Is Active in Human Amniotic Fluid Stem Cells - Rodrigues, Melissa (Stem Cells Dev, 2018)
Despite increasing interest in human amniotic fluid cells, very little is known about the regulation and function of p53 in this cell type. In this study, we show that undifferentiated human amniotic fluid cells express p53, yet at lower levels than in cancer cells. The p53 protein in amniotic fluid cells is mainly localized in the nuclei, however, its antiproliferative activity is compromised in these cells. Igf2, a maternal imprinted gene, and c-jun, a proto-oncogene, are regulated by p53 in these cells. DNA damage leads to an increase in p53 abundance in human amniotic fluid cells and to transcriptional activation of its target genes. Interestingly, cell differentiation toward the neural lineage leads to p53 induction as differentiation progresses.